Cooperation or conflict in northeast Asia? - An approach of NARCI (Northeast Asia Regional Cooperation Index) - Jiyoung Moon; Jehoon Park; Sunghoon Park (Asia and the Global Economy)
In order to measure the current status of Northeast Asian regional cooperation, more specifically in order to comprehensively evaluate whether the region is in a state of cooperation or conflict, this paper adopts a revised and improved combination of approaches used in three existing publications. The Northeast Asia Cooperation Index (NARCI) illustrates the strained situation in Northeast Asia as expected. Looking at the total score, it is -0.25 and -0.425 in 2022 and 2023, respectively, indicating that Northeast Asian regional cooperation is in a state of conflict rather than cooperation and is getting worse. In particular, the political and security situation is at its worst and the economy is also depressed. Regional trade, investment and energy cooperation are all deteriorating. However, some indicators point to the obvious contrast between cooperation and conflict in Northeast Asia giving unexpected dynamism. It should be emphasized that the regional value chain remains robust, even amid the conflict between the US and China.